Relationship between range of motion, strength, motor control, power, and the tennis serve in competitive-level tennis players: A pilot study - Palmer, K.; Jones, D.; Morgan, C.; Zeppieri, G. (Sports Health: A Multidisciplinary Approach, 2018)
Background: The tennis serve is a complex skill requiring appropriate energy transfer to maximize serve speed. As the only independently powered shot in tennis, it is important to understand what characteristics contribute to a player`s serve. Hypothesis: Upper extremity and lower extremity power variables will be predictive of serve speed. Study Design: Cross-sectional study. Level of Evidence: Level 3. Methods: A total of 42 competitive tennis players underwent range of motion, strength, motor control, power, and serve speed testing. Motion assessment was completed for shoulder external and internal rotation, trunk rotation, hip external and internal rotation, and ankle dorsiflexion. Strength was assessed for the rotator cuff, scapula, and hip musculature. Motor control was evaluated through upper and lower extremity Y-balance testing. Power assessments were made using broad jump, single-leg hop, and seated unilateral shot put testing. Pearson correlation was conducted to assess associations of skill, height, and tested variables to serve speed. Significant variables were used in a stepwise linear regression model, with serve speed as the dependent variable. Variables are listed in relation to the participant`s dominant arm. Results: Skill, height, contralateral hip external rotation range of motion, nondominant arm Y-balance anterolateral reach, bilateral single-leg hops, and seated unilateral shot put throws for both arms demonstrated significant positive correlations to serve speed (P < 0.05). Serve speed was predicted with 84% variance through skill, height, contralateral hip external rotation range of motion, ipsilateral single-leg hop, and the seated unilateral shot put throws. Conclusion: The ability to generate increased serve speed is multifactorial. The combination of skill, height, hip motion, and upper and lower extremity power may determine serve speed. Clinical Relevance: The findings suggest that motion, motor control, and power testing should be evaluated when working with this population to improve serve speed.